Corrigendum. (September 2016) - Unknown
Corrigendum to 'Understanding the development of Chinese EFL learners' email literacy through Exploratory Practice' by Yuan-shan Chen, Language Teaching Research, 2016, 20(2): 165–180. DOI:10.1177/1362168814562014 . In March 2016 issue of Language Teaching Research, in the above mentioned article, the author would like to add the following clarification to the section which describes the collaborative e-mail construction activity and its outcome (pp. 173–174): 'To assist the students in their joint construction activity, they were presented with a writing sample from a previous cohort of students who had engaged in a similar sequence of activities as those described in this article. Although the students were found to copy parts of this example as they constructed their own text, their appropriate decisions of which parts to copy and which to modify can nonetheless be considered a sign of their developing pragmatic awareness.'